2015
DOI: 10.18632/oncotarget.3549
|View full text |Cite
|
Sign up to set email alerts
|

Independent replication of a melanoma subtype gene signature and evaluation of its prognostic value and biological correlates in a population cohort

Abstract: Development and validation of robust molecular biomarkers has so far been limited in melanoma research. In this paper we used a large population-based cohort to replicate two published gene signatures for melanoma classification. We assessed the signatures prognostic value and explored their biological significance by correlating them with factors known to be associated with survival (vitamin D) or etiological routes (nevi, sun sensitivity and telomere length). Genomewide microarray gene expressions were profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 34 publications
6
53
0
Order By: Relevance
“…Nsengimana et al performed an independent validation of a whole-genome mRNA profiling classification. 17,18 Archival tumor tissues from 300 patients (224 primary and 76 metastatic) were evaluated. Gene signature classification was significantly correlated with Breslow thickness, ulceration, mitotic rate, and melanoma-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nsengimana et al performed an independent validation of a whole-genome mRNA profiling classification. 17,18 Archival tumor tissues from 300 patients (224 primary and 76 metastatic) were evaluated. Gene signature classification was significantly correlated with Breslow thickness, ulceration, mitotic rate, and melanoma-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…microscopic ulceration . A recent study showed that absence of primary CMM ulceration was independently associated with longer progression‐free survival (PFS) but not overall survival (OS) in Stage IV CMM‐patients treated with MAPK‐inhibitors . Ulceration status has earlier also been correlated to treatment outcome, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The "High-Immune" group was distinguished by elevated expression of immune genes, the "Normal-like" group by genes expressed in surrounding normal cells, the "MITF-high Pigmentation" and the "MITF-low Proliferative" groups displayed increased expression of cell-cycle genes, while the "MITF-low Proliferative" group had decreased expression of melanocyte differentiation genes. These subtypes were derived in stage IV tumors (Jönsson et al, 2010), but have since been recapitulated and firmly established in primary tumors (Harbst et al, 2012;Nsengimana et al, 2015) and stage III tumors (Cirenajwis et al, 2015). In 2015, the TCGA landmark study reported three melanoma gene expression subtypes (Cancer Genome Atlas Network, 2015).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The TCGA "Keratin" group consisted predominantly of the Lund "Normal-like" and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 "MITF-high Pigmentation" groups, while the TCGA group "MITF-low" contained 76% of the Lund "MITF-low Proliferative" tumors. Next, we applied the TCGA subtypes to the published Bergen (Jönsson et al, 2010)(GSE33153), Lund (Cirenajwis et al, 2015)(GSE65904) and Leeds (Nsengimana et al, 2015)(E-MTAB-4725) datasets, which have pre-existing Lund subtype classifications. The fraction of subtypes differed between datasets, in accordance to specimen site.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%